Edukasi Kebersihan Diri sebagai Upaya Pencegahan Dermatofit pada Siswa di SDK Kristen Raja Desa Teunbaun Kabupaten Kupang - Sintha Purimahua; Grace Maku; Yudishinta Missa; Grouse Oematan (GOTAVA, 2024)
Community service activities carried out in Teunbaun Village, Kupang Regency, aim to increase the knowledge and understanding of Christ Raja Elementary School students about personal hygiene and skin diseases, especially dermatophytes. Through educational activities held for 30 students in grades 5 and 6, the service team succeeded in increasing students' understanding of risk factors, symptoms and prevention of skin diseases. The results of the education carried out show an increase in students' knowledge and understanding. Personal hygiene practices such as bathing, brushing teeth and washing hands regularly are seen as one of the efforts that can be taken to prevent the spread of germs and increase the risk of skin diseases. Furthermore, educational activities like this need to be carried out on an ongoing basis to increase students' understanding and awareness of the importance of maintaining health.